Akron's Daily Miracle : Reporting the News in the Rubber City - Warner, Stuart (Stuart Hunt); Van Tassel Warner, Deb (Book collections on Project MUSE., 2020)
"Akron's Daily Miracle begins with the death of the heir to John S. and James Knight's newspaper empire and ends with the demise of Knight Ridder Newspapers but also with a note about how the Knight spirit lives on in Akron and elsewhere. The Beacon Journal staff discuss how they came together to produce the Pulitzer Gold Medal-winning series A Question of Color; what it was like to walk behind Akron's Lebron James in the parade of champions in Cleveland; and the impact of being the largest city in America without a local TV station. In between is a collection of essays from those who produced the news in the Rubber City, including international best-selling authors Thrity Umrigar and Regina Brett and popular columnists Bob Dyer and Stuart Warner, written to remind readers of the value of excellent local journalism."--Publisher's description.